Jurisdiction in international law - Ryngaert, Cedric (Oxford : Oxford University Press, 2008)
Analysing developments across antitrust, criminal and human rights law, this text explains how the principles of sovereignty and territoriality have been undermined, and develops a new theory of international jurisdiction based on the concept of subsidiarity.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Jurisdiction (International law); Jurisdiction, Territorial; Criminal jurisdiction